2013
DOI: 10.1002/nau.22369
|View full text |Cite
|
Sign up to set email alerts
|

Turkish adaptation of the short form of the pelvic organ prolapse/urinary incontinence sexual function questionnaire (PISQ‐12): A validation and reliability study

Abstract: The Turkish version of the PISQ-12 is a reliable, consistent and valid instrument to assess sexual function in women with urinary incontinence and/or pelvic organ prolapse. It is also a comprehensive and easily applicable instrument which as a treatment outcome or research tool in clinical practices.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(7 citation statements)
references
References 28 publications
1
5
0
Order By: Relevance
“…The internal consistency of the partner-related scale was lower than that of the total score and both the behavioral-emotive scale and the physical scale, even after correction for item 12. This was also found in previous translations of the PISQ-12 [ 15 , 10 ]. It should be noted that the partner-related scale evaluates the physical sexual function related to the partner.…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…The internal consistency of the partner-related scale was lower than that of the total score and both the behavioral-emotive scale and the physical scale, even after correction for item 12. This was also found in previous translations of the PISQ-12 [ 15 , 10 ]. It should be noted that the partner-related scale evaluates the physical sexual function related to the partner.…”
Section: Discussionsupporting
confidence: 86%
“…Cronbach’s alpha was 0.69 in the patient group and 0.57 in the reference group. Other studies validating the PISQ-12 in different languages have shown higher Cronbach’s alpha values, ranging from 0.71 to 0.79 [ 15 , 13 , 14 , 10 ]. The lower value found in this study originated from the partner-related item scale, probably due to the alteration of item 12.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The PISQ-12 is a reliable, validated and easily applicable form of questionnaire and enables an evaluation of women's sexual functions [9]. We used a Turkish translation of the PISQ-12 to assess sexual functions [10]. We applied the POP-Q scoring system as defined by the International Continence Society [11].…”
Section: Methodsmentioning
confidence: 99%
“…The total score achievable in the questionnaire ranges between 0-48. A high score indicates better sexual function ( 16 ) .…”
Section: Methodsmentioning
confidence: 99%